1977
DOI: 10.1177/107118137702100501
|View full text |Cite
|
Sign up to set email alerts
|

Task Taxonomy: Two Ignored Issues

Abstract: This paper focuses on two major issues concerning task taxonomies which to date have been ignored. The first issue involves the development of a set of criteria for the evaluation of existing and future task taxonomies. A set of criteria is proposed and several major existing taxonomies are evaluated. The second issue concerns the relation of empirical data, provided by field and laboratory research, to the development of the task taxonomy. Three approaches are cited which seem to encompass the relation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The essential goal of task analysis is systematically to define the relevant points of transaction between the human operator and the environment in ways which specify what is being accomplished and what purpose it serves. Although such analyses most often involve observation and classification of behavior in terms of some schema, there is no single universal approach used for task analysis (Companion & Corso, 1977;Fleishman, 1982).…”
Section: Human Factors Research: Characteristic Problems and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The essential goal of task analysis is systematically to define the relevant points of transaction between the human operator and the environment in ways which specify what is being accomplished and what purpose it serves. Although such analyses most often involve observation and classification of behavior in terms of some schema, there is no single universal approach used for task analysis (Companion & Corso, 1977;Fleishman, 1982).…”
Section: Human Factors Research: Characteristic Problems and Methodsmentioning
confidence: 99%
“…This taxonomy can then be used to develop frequency distributions indicating the number of times in a meal preparation the person accomplished a discrete task. This stage of the system admittedly violated Companion and Corso's (1977) point regarding generalizability of descriptors. However, activity-specific content in descriptors was needed to help judges define the tasks as a precursor to second phase characterization of them in more generalizable terms.…”
Section: Task Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the 14 factors, identified by our tax)nomic survey do meet the basic criteria of thcorctical and operational applicability in regard to the assessment of aviator proficiency (7).…”
Section: Abstro:tmentioning
confidence: 99%